Optimalisasi Sosialisasi Program Pencegahan Stunting pada Ibu Hamil dan Anak-Anak di Desa Katulisan Serang Banten - Dhany Isnaeni Dharmawan; Syamsudin Syamsudin; Ahmad Zainuri; Abdul Fatah; Ahmad Firdaus (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2023)
The Indonesian government has launched the National Action Plan program for handling stunting at the national level with the theme "National Action Plan Program for handling stunting at the national level" in 2023 which is focused on regions, especially villages in Indonesia. One part of the program is the prevention of stunting that occurs in the community. Because most people do not understand properly about stunting, and think that stunting or dwarfism, the term commonly used in society, is a hereditary factor. This community service activity is carried out to increase knowledge and understanding as well as community participation in the prevention and early detection program for stunting in toddlers which is expected to directly motivate the community to participate in paying attention to the growth and development of their children so that their growth and development can be optimal. The method used was to assess community knowledge and the problems faced regarding prevention and how to assess/early detect stunting in toddlers in Katulisan Village, Cikeusal District, Serang Banten. Mother's knowledge was measured using a pre-test before the activity and a post-test after being given the knowledge.